Implementation of minimum health service standards on health service coverage for educational age the basis and its influence on student health status - Astutik, Yeni Widi; Ratu, Jacob M.; Nayoan, Christina R. (Journal of Evidence-based Nursing and Public Health, 2025)
Background: Minimum Service Standar Health for basic education age health services is one of the 12 minimum service standards in the health sector that must be provided by district/city governments to every citizen with a target of 100% achievement. Findings: However, in 2023, the achievement of the minimum service standar target has not been met for the Kupang City Government so that citizens aged 7-15 years have not fully received basic health services. The aim of this research is to find out how the implementation of Minimum Service Standar Health in primary education age health services in Kupang City and its relationship with students' health status. Methods: This research is a mixed method research with data collection techniques in the form of filling out questionnaires, interviews and desk reviews conducted at Penfui Health Center, Oepoi Health Center, Oebobo Health Center, Kupang City Health Center and Oesapa Health Center. The sample in the study was 45 people consisting of Heads of Community Health Centers, Community Health Center Health Workers, School Health Business/Usaha Kesehatan Sekolah (UKS) Managers and Teachers. Conclusion: The results of statistical tests show that there is a significant relationship between the variables communication (p=0.03), resources (p=0.018), disposition (p=0.020), bureaucratic structure (p=0.037) on Health Service Coverage at Primary Education Age. Meanwhile, the health service coverage variable for primary education age has no relationship with students' health status (p=0.167). Novelty/Originality of this article: So it is necessary to increase outreach activities from health workers to parents, families and the community in order to increase understanding and awareness about the importance of health checks at the primary education age so that activities can be carried out well and students benefit from these activities.